2003
DOI: 10.1046/j.1540-6261.2003.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Momentum Investing and Business Cycle Risk: Evidence from Pole to Pole

Abstract: We examine whether macroeconomic risk can explain momentum profits internationally. Neither an unconditional model based on the Chen, Roll, and Ross (1986) factors nor a conditional forecasting model based on lagged instruments provides any evidence that macroeconomic risk variables can explain momentum. In addition, momentum profits around the world are economically large and statistically reliable in both good and bad economic states. Further, these momentum profits reverse over 1‐ to 5‐year horizons, an act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
392
13
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 818 publications
(479 citation statements)
references
References 51 publications
(121 reference statements)
55
392
13
6
Order By: Relevance
“…Similar to the Studies by Kho et al (1997), Chui, Titman and Wei (2000), Griffin and Martin (2003), C. Liu and Lee (2001), Du et al (2009), etc., our results suggested that there was no evidence of return continuation in TSE and using momentum strategy has created negative returns in all periods. In addition, considering the liquidity required to form momentum portfolios, we observed that the liquidity factor has no effect on profitability of the momentum strategy, and using this strategy taking into account, liquidity have generated negative returns in TSE in all periods.…”
Section: Resultssupporting
confidence: 75%
“…Similar to the Studies by Kho et al (1997), Chui, Titman and Wei (2000), Griffin and Martin (2003), C. Liu and Lee (2001), Du et al (2009), etc., our results suggested that there was no evidence of return continuation in TSE and using momentum strategy has created negative returns in all periods. In addition, considering the liquidity required to form momentum portfolios, we observed that the liquidity factor has no effect on profitability of the momentum strategy, and using this strategy taking into account, liquidity have generated negative returns in TSE in all periods.…”
Section: Resultssupporting
confidence: 75%
“…These findings are robust as confirmed by Rouwenhorst (1998) and Griffin, Ji, and Martin (2003) who find momentum in international markets. Fama and French (1993) state market, value, and size factors cannot account for momentum returns.…”
Section: Review Of Related Literaturesupporting
confidence: 66%
“…Rouwenhorst (1998) found evidence supporting the existence of momentum strategies in 12 European countries during the period 1980-1995, additional evidence has been obtained from the Australian market (Hurn & Pavlov, 2003). In addition Griffin et al (2003) measured momentum profits internationally, by taking samples from all the continents, and the results showed that momentum profits are significant in all regions except Asia with emerging market showing weaker profits compared to developed ones.…”
Section: Momentummentioning
confidence: 84%